Kynurenine acid - metabolism and regulation of kynurenine pathway - Kozłowski, Piotr; Kozlowska, Magdalena (Journal of Education, Health and Sport, 2017)
Kynurenic acid (KYNA) was first isolated from the dog's urine in 1853 by german chemist Justus von Liebig. KYNA probably plays an important role in the pathogenesis of many neurodegenerative and psychiatric diseases. Its elevated concentration were found in the brain (post mortem) or in the cerebrospinal fluid patients with schizophrenia, bipolar disorder, Alzheimer's disease, meningitis, autoimmune diseases, inflammatory processes and memory and learning disorders. The reduced KYNA concentration is characteristic for multiple sclerosis, Parkinson's disease, Huntington's disease and epilepsy. KYNA is an organic compound naturally occurring in nature. This amino acid belongs to the group of exogenous amino acids and can be synthesized by plants and bacteria alone. The largest amount of tryptophan about 95%is metabolised by the kynurenine pathway. Only 1% of tryptophan supplied in the diet serves to produce serotonin in the brain. The process of regulation of KYNA synthesis in both the CNS and the periphery is complicated.